2017
DOI: 10.4236/ce.2017.89105
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the State of Creativity and Critical Thinking in Engineering Undergraduates

Abstract: The goal of an undergraduate engineering education is to provide students with the necessary knowledge and skills needed to solve real world problems. Creativity and critical thinking are two abilities essential for success in the workplace, and are highly sought after by employers. However, there is evidence of decreasing creativity and critical thinking in senior engineering students. This study sought to understand if freshman engineering students are measurably more creative, but less capable of critical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 68 publications
1
32
0
Order By: Relevance
“…Atwood and Pretz (2016) found that creative ability was not predictive of first or final year grade point average (GPA) for engineering students, suggesting that it does not play a substantial role in engineering course assessment. Two recent studies (Genco, Hölttä-Otto, & Seepersad, 2012;Sola, Hoekstra, Fiore, & McCauley, 2017) demonstrated that first year students in engineering courses were capable of significantly greater creativity on design and divergent thinking tasks than seniors, suggesting that either more creative students leave engineering programs before their senior year or undergraduate engineering education may actually contribute to a decline in creativity over 4 years of college. The traditional structure of post-secondary engineering education may prove particularly difficult for students who struggle in such environments, including those with attention deficit hyperactivity disorder (ADHD; Dipeolu, 2011;Honken & Ralston, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Atwood and Pretz (2016) found that creative ability was not predictive of first or final year grade point average (GPA) for engineering students, suggesting that it does not play a substantial role in engineering course assessment. Two recent studies (Genco, Hölttä-Otto, & Seepersad, 2012;Sola, Hoekstra, Fiore, & McCauley, 2017) demonstrated that first year students in engineering courses were capable of significantly greater creativity on design and divergent thinking tasks than seniors, suggesting that either more creative students leave engineering programs before their senior year or undergraduate engineering education may actually contribute to a decline in creativity over 4 years of college. The traditional structure of post-secondary engineering education may prove particularly difficult for students who struggle in such environments, including those with attention deficit hyperactivity disorder (ADHD; Dipeolu, 2011;Honken & Ralston, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefor it is important to focus on this phase and to study effects of the method to different students groups as we want to prepare our students in the best possible way to generate added value to the current design practice in industry. The literature review (Ho 2001, Ahmed et al, 2003, Goldtschmidt 2013, Björklund 2013, Seidel and Fixson 2013, Kok et al, 2016, Self et al, 2017, Sola et al, 2017, Mosely et al, 2018, Jagtap 2018, Kierman et al, 2019 suggests a significant difference between both student groups, novice and more experienced ones, therefor made it interesting to further research this aspect. Our main aim is therefor to investigate the effect of the proposed design method to different student groups, especially Bachelor and Master students to see whether the method is more effective for one of the groups.…”
Section: Figure 3 An Example Of the Transformation Of The Individualmentioning
confidence: 99%
“…After initial ideas are developed in step (3), they are conceptually evaluated before step (4). The prototype is explicitly evaluated in step (6) to quantify how well it meets the design criteria. This is largely an objective evaluation but may include subjective judgment for certain design criteria (e.g.…”
Section: The Engineering Design Processmentioning
confidence: 99%
“…Troublingly, however, there is evidence that those graduating from engineering programs are less creative than those who begin. 5,6 One reason for this may be the traditional focus of engineering education on specific procedures applied to wellconstrained problems in which there is a single correct answer. 7 As Surovek and Rassati state, "focusing predominately on developing analytical skills at the expense of variable solution approaches limits the development of the divergent thinking skills needed for innovation."…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation